Composition of plastic waste in construction industry / Nor Alya Atiqah Mohidin and Muhammad Naim Mahyuddin - Mohidin, Nor Alya Atiqah; Mahyuddin, Muhammad Naim (2019)
This paper aims to study the issue and problem of plastic waste and to identify its composition in new or existing products. The continuous demand of plastics caused the plastic waste accumulation in the landfill consumed a lot of spaces that contributed to the environmental problem. The ranking of the highest to the lowest plastic waste in municipal solid waste according to the categories of plastic containers. Some alternatives that have been developed to manage plastic wastes were recycling and innovation in construction industry. The innovations in construction industry may get a place to contribute as a solution for reducing plastic waste on earth. It's given a new value and price which may improve the economic growth. The innovation of plastic waste into new products can be applied either in production, building components or construction materials.